KARAKTERISASI FISIKOKIMIA CTMP BERTANDA TEKNESIUM-99m SEBAGAI RADIOFARMAKA PENYIDIK KANKER TULANG - Isti Daruwati; Misyetti Misyetti; Maula Eka Sriyani (Pusbindiklat - LIPI, 2009)
Radiopharmaceutical for bone cancer seeking was developed in variable phosphonate compound labeled with technetium-99m, formally pyrophosphate and diphosphonate compound. Either pyrophosphate or diphosphonate still unsatisfied to use as radiopharmaceuticals for bone seeking agent because the high accumulation in lever, muscle and blood. CTMP have higher affinity than others. The Physicochemical characterization of 99